External workloads vary by position and game result in us-based professional soccer players - Long, G. M.; Joyce, S. M.; Herrington, R. T.; Fox, K. B.; Mumaugh, J. E. (International Journal of Exercise Science, 2023)
Professional soccer is a physically demanding sport that requires players to be highly trained. Advances using GPS allow the tracking of external workloads for individual players in practice and competition, however, there is a lack of evidence on how these measures impact match results. Therefore, we analyzed external workloads by player position and determined if they vary depending on the result of competitive matches. External workloads were analyzed in professional soccer players (n = 25) across 28 competitive games. One-way ANOVA determined if workloads varied by position (striker - ST, wide midfielder - WM, central midfielder - CM, wide defender - WD, central defender - CD) or across games won (n = 8), lost (n = 13) or tied (n = 7). Repeated-measures ANOVA assessed differences in workloads specific to each position in each of the result categories. Statistical significance was set at p < 0.05. Across all games, more high-speed and very-high speed running was done by ST and WD compared to CD (p < 0.001) and CM (p < 0.001 - 0.02). Whole-team data showed no differences in any external workload variable with respect to match result (p > 0.05), however, in games won ST did more very high-speed running than in losing games (p = 0.03) and defending players did more high and very high-speed running in games tied vs. those won or lost (p < 0.05). Whole-team external workloads do not vary depending on the match result; however, high speed running may be a differentiating factor at the positional level. Coaches should consider position-specific analysis when examining player workloads.